Growth variability in Atlantic horse mackerel Trachurus trachurus (Linneus, 1758) across the central Mediterranean Sea: contrasting latitudinal gradient and different ecosystems - Basilone, Gualtiero; Ferreri, Rosalia; Aronica, Salvatore; Bonanno, Angelo; Genovese, Simona; Rumolo, Paola; Carbonara, Pierluigi; Barra, Marco (Frontiers in Marine Science, 2023)
Data on Atlantic horse mackerel Trachurus trachurus (Linneus, 1758) were collected along 8-year acoustic surveys (2011-2018). Age and growth variability of horse mackerel from the Central Mediterranean Sea were investigated within different, contrasting habitats, from the south of Sicily to the north Tyrrhenian (Ligurian Sea). Data from satellite provided the habitat features along the study period over the whole surveyed area. For comparison purposes, according to the ecosystems difference the study area has been split into four subareas: Strait of Sicily (SoS), North of Sicily (NS), south Tyrrhenian Sea (ST) and north Tyrrhenian Sea (NT). In terms of the FAO Geographical Sub-Area definition the SoS corresponding to GSA15 and 16, NS to GSA 10 south, ST to GSA10 north and NT to GSA 9. Results showed a growth homogeneity in the study area, suggesting a unique stock inhabiting these waters. The only exception was recorded for juveniles (Age 0 class) in the SoS, where a lower size at age was detected compared to other areas. A multiple linear modelling analyses suggested that variability in length at age 0 was mainly linked to the oceanographic differences between an upwelling driven system (Strait of Sicily) and the other ecosystems, where enrichment processes are mainly due to river runoff (relevant in ST and NT). Namely, Absolute Dynamic Topography (ADT) and body condition factor (Kn) were significantly related to differences in length at age 0. Results revealed that currents (and gyres) are among the principal abiotic factors controlling Atlantic horse mackerel growth in its first year of life, suggesting that circulation and food-related processes (i.e., zooplankton concentration) are of major importance for this species. Finally preliminary observations suggest the Strait of Sicily may be the main spawning area among those analysed.